Measurements of projectile fragments from 70 Zn (15 MeV/nucleon) + 64 Ni collisions with the MAGNEX spectrometer at INFN-LNS - Koulouris, Stergios; Souliotis, Georgios; Cappuzzello, Francesco; Carbone, Diana; Pakou, Athena; Agodi, Clementina; Brischetto, Giuseppe; Calabrese, Salvatore; Cavallaro, Manuela; Ciraldo, Irene; Fasoula, Olga; Klimo, Jozef; et al. (HNPS Advances in Nuclear Physics, 2022)
The present work is focused on our efforts to produce and identify neutron-rich rare isotopes from peripheral reactions below the Fermi energy. High-quality experimental data were obtained from a recent experiment with the MAGNEX spectrometer at INFN-LNS in Catania, Italy. The main goal of this effort is to describe the adopted identification techniques used to analyze the data from the reaction 70 Zn (15 MeV/nucleon) + 64 Ni. The particle identification procedure is based on a novel approach that involves the reconstruction of both the atomic number Z and the ionic charge q of the ions, followed by the identification of the mass. Our method was successfully applied to identify neutron-rich ejectiles from multinucleon transfer in the above reaction 70 Zn + 64 Ni at 15 MeV/nucleon. The analysis of the data is ongoing. We expect to obtain the angular and momentum distributions of the fragments, along with their production cross sections. These data, along with comparisons with theoretical models are expected to contribute to a better understanding of the complex reaction mechanisms of multinucleon transfer that dominate this energy regime.